Die Existenzbedingungen der verallgemeinerten automorphen Funktionen und eine Randwertaufgabe Carlemans - Kabaila, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Кабайла. Условия существования обобщенных автоморфных функций и краевая задача Карлемана V. Kabaila. Apibendrintų automorfinių funkcijų egzistavimo sąlygos ir Karlemano kraštinis uždavinys